No Effect of Acupuncture in the Relief of Delayed-Onset Muscle Soreness: Results of a Randomized Controlled Trial. Issue 6 (November 2016) - Fleckenstein, Johannes; Niederer, Daniel; Auerbach, Kerstin; Bernhörster, Marcus; Hübscher, Markus; Vogt, Lutz; Banzer, Winfried
Abstract : Background: Delayed-onset muscle soreness (DOMS) is a common symptom in people participating in exercise, sport, or recreational physical activities. Several remedies have been proposed to prevent and alleviate DOMS. Design and Methods: A five-arm randomized controlled study was conducted to examine the effects of acupuncture on eccentric exercise-induced DOMS of the biceps brachii muscle. Participants were recruited through convenience sampling of students and general public. Participants were randomly allocated to needle, laser, sham needle, sham laser acupuncture, and no intervention. Outcome measures included pressure pain threshold (PPT), pain intensity (visual analog scale), and maximum isometric voluntary force. Results: Delayed-onset muscle soreness was induced in 60 participants (22 females, age 23.6 ± 2.8 years, weight 66.1 ± 9.6 kg, and height 171.6 ± 7.9 cm). Neither verum nor sham interventions significantly improved outcomes within 72 hours when compared with no treatment control ( P > 0.05). Conclusions: Acupuncture was not effective in the treatment of DOMS. From a mechanistic point of view, these results have implications for further studies: (1) considering the high-threshold mechanosensitive nociceptors of the muscle, the cutoff for PPT (5 kg/cm 2 ) chosen to avoid bruising might have led to ceiling effects; (2) the traditional acupuncture regimen, targeting muscle pain, might have been inappropriate as the DOMS mechanisms seem limited to the muscular unit and its innervation. Therefore, a regionally based regimen including an intensified intramuscular needling (dry needling) should be tested in future studies, using a higher cutoff for PPT to avoid ceiling effects.